Design of Improved Fuel Cell Controller for Distributed Generation Systems - Olsen Berenguer, Fernando Adrian (2010)
The world has been undergoing a deregulation process which allowed competition in the electricity generation sector. This situation is bringing the opportunity for electricity users to generate power by using small-scale generation systems with emerging technologies, allowing the development of distributed generation (DG). A fuel cell power plant (FCPP) is a distributed generation technology with a rapid development because it has promising characteristics, such as low pollutant emissions, silent operation, high efficiency and long lifetime because of its small number of moving parts. The power conditioning system (PCS) is the interface that allows the effective connection to the electric power system. With the appropriate topology of the PCS and its control system design, the FCPP unit is capable of simultaneously performing both instantaneous active and reactive power flow control. This paper describes the design and implementation of a novel high performance PCS of an FCPP and its controller, for applications in distributed generation systems. A full detailed model of the FCPP is derived and a new three-level control scheme is designed. The dynamic performance of the proposed system is validated by digital simulation in SimPowerSystems (SPS) of MATLAB/Simulink.